Perception of Service Quality, Price, and Conservation Value Based on Wildlife Value Orientation on the Intention to Return to Bali Bird Park Gianyar - Pratisthita, Dewa Ayu Abhinandati Prajna; Damayanti, Titien; Liestiandre, Hanugerah Kristiono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of service perception and price, conservation value based on Wildlife Value Orientation based on the intention to revisit Bali Bird Park Gianyar. Using a quantitative approach, the research was sampled using a purposive sampling technique, with respondents as many as 450 tourists who had visited Bali Bird Park Gianyar. Data analysis was carried out using the Structural Equation Modeling Partial Least Square (SEM-PLS) approach. The results of the study showed that the p-value was less than 0.05, which was 0.000 with a t-statistic above 1.96 which means: (1) the perception of service quality has a positive effect on the intention to revisit, (2) the perception of price has a positive effect on the intention to visit again, (3) the perception of service quality has a positive effect on the perception of price perception, (4) the perception of service quality has a positive effect on the perception of conservation value, (5) the perception of price has a positive effect on the perception of the value of conservation, (5) the perception of price has a positive effect on the perception of the value of the Perception of conservation value, (6) perception of conservation value has a positive effect on intention to return, (7) perception of conservation value mediates positively the effect of perception of service quality on intention to revisit, (8) perception of conservation value mediates positively the influence of price perception on intention to revisit, and (9) price perception mediates positively the effect of perception of service quality on the perception of conservation value.